A nomogram prediction of coronary artery dilation in Kawasaki diseases based on mtDNA copy number - Peng, Mou; Yue, Peng; Zhang, Yue; Li, Hong; Hua, Yimin; Li, Yifei; Zheng, Hong; Liu, Fangfei (Frontiers in Immunology, 2024)
Objective: The level of mitochondrial DNA copy number (mtDNA-CN) in peripheral blood cells had been identified to be involved in several immune and cardiovascular diseases. Thus, the aim of this study is to evaluate the levels of mtDNA-CN in Kawasaki disease (KD) and to construct a nomogram prediction for coronary artery lesions in children with KD.Methods: One hundred and forty-four children with KD diagnosed from March 2020 to March 2022 were involved in the study. The clinical features and laboratory test parameters of these children were assessed between the KD and normal groups.Univariable and multivariable analyses were performed sequentially to identify the essential risk factors. Subsequently, a nomogram prediction was constructed.Results: A total of 274 children were included in the analysis. Of these, 144 (52.6%) represented the KD group. Peripheral blood DNA mtDNA qPCR showed that the -log value of mtDNA-CN in the KD group (6.67±0.34) was significantly higher than that in the healthy group (6.40±0.18) (P<0.001). The area under the ROC curve for mtDNA-CN in distinguishing KD was 0.757. MtDNA-CN (OR = 13.203, P = 0.009, 95% CI 1.888-92.305), RBC (OR = 5.135, P = 0.014, 95% CI 1.394-18.919), and PA (OR = 0.959, P = 0.014, 95% CI 0.927-0.991) were identified as independent risk factors for coronary artery dilation in children with KD. Finally, the nomogram predictive was established based on the results of multivariable analysis, demonstrating the satisfied prediction and calibration values.The results of this study revealed that mtDNA-CN could be used as a biomarker in predicting the development of KD. Furthermore, the higher the mtDNA-CN was significantly associated with coronary artery dilation in KD.